2018
DOI: 10.14716/ijtech.v9i7.2644
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Applicability of Gamification and Game-based Learning to Improve Household-level Waste Management Practices among Schoolchildren

Abstract: Knowledge strongly affects attitudes toward waste management; thus, embedding an environmental mentality at a young age is crucial. Game-based interventions, such as gamification and game-based learning, have huge potential to be effective learning tools. This paper examines the potential of gamification to improve waste management practices among schoolchildren through a narrative review of 25 papers on gamification for waste management and gamification for schoolchildren. The effectiveness of game-based lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Serious gaming and gamification have been implemented in higher education students in a social science subject, which established that the two instructions effective in educational innovation were chiefly the aspects of engagement and motivation (C ozar-Gutiérrez and S aez-L opez, 2016). A waste management study for school children reported serious gaming and gamification instructions to have a positive impact on attitude change on environment mentality at a young age (Magista et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Serious gaming and gamification have been implemented in higher education students in a social science subject, which established that the two instructions effective in educational innovation were chiefly the aspects of engagement and motivation (C ozar-Gutiérrez and S aez-L opez, 2016). A waste management study for school children reported serious gaming and gamification instructions to have a positive impact on attitude change on environment mentality at a young age (Magista et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…The participants (in decentralizedcomputer-terminal form) are connected by using key-access system enabling direct transactions between sellers and buyers without intermediaries [12]. Because blockchain nature is a distributed ledger database, there are many things that can be improved by using blockchain such as big data for data analysis [13,14].…”
Section: Blockchainmentioning
confidence: 99%
“…The participants (in decentralized-computer-terminal form) are connected by using a key-access system enabling direct transactions between sellers and buyers without 6 intermediaries [9]. Many processes can be improved by using blockchain, such as the analysis of big data [10,11]…”
Section: Blockchainmentioning
confidence: 99%